Persepsi Pedagang Pasar Inpres Sadabuan Terhadap Baitul Mal Wat Tamwil (BMT) Insani Padangsidimpuan - Sari, Dewi Purnama; Nofinawati, Nofinawati; Lubis, Delima Sari (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Inpres Sadabuan market traders in the city of Padangsidimpuan are indicated to have different perceptions of BMT Insani Padangsidimpuan. This study aims to determine the extent to which the Inpres market traders' perceptions of Baitul Mal Wat Tamwil (BMT) Insani Padangsidimpuan. The time of this research was carried out from October to July 2018 in the City of Padangsidimpuan. This type of research is qualitative research, the data source used by the researcher is primary data, namely the Inpres Sadabuan market traders, data collection techniques by interview, the data analysis technique of this research is to systematically search and compile data obtained from interviews, and field observations. The results of this study indicate that services at Insani Padangsidimpuan BMT can be said to be good with a figure of 70%, and BMT Insani Padangsidimpuan has a product based on the principles of Islamic law with a figure of 30%, and the traders' views on the financing procedure at BMT Insani Padangsidimpuan can be said to be easy with a figure of 90%. , and the profit at BMT Insani Padangsidimpuan can be said to be high at 80%.Key words: Perception, traders, and BMT Insani Padangsidimpuan.